Discovery of Vascular Endothelial Growth Factor Receptor‐2 (VEGFR‐2) Inhibitors by Ligand‐based Virtual High Throughput Screening. Issue 7 (13th March 2020) - Selvam, Chelliah; Mock, Charlotta D.; Mathew, Omana P.; Ranganna, Kasturi; Thilagavathi, Ramasamy
Abstract: Virtual screening has become one of the important tools in the discovery of novel hits for the given target. The present study reports the successful application of ligand‐based virtual screening method for the discovery of novel vascular endothelial growth factor receptor‐2 (VEGFR‐2) inhibitors. We generated a ligand query model with pharmacophore features from the reported VEGFR‐2 inhibitors using vROCS tool and performed virtual screening. Among the 2.4 million lead like molecules of ZINC database screened, nineteen prioritized compounds were purchased from Enamine and ChemBridge and tested for VEGFR‐2 inhibitory activity using Promega's ADP‐Glo™ kinase assay. Experimental validation led to the discovery of four compounds 3, 7, 10, and 13 . Compound 10 exhibited moderate inhibitory activity with the IC50 value of 19.3 μM. Molecular docking was performed for these compounds and the predicted binding modes reported in this paper may further guide to explore the possible structural changes to get more potent VEGFR‐2 inhibitors Abstract :